Proses Penerimaan Diri Pada Remaja Tunadaksa Berprestasi Yang Bersekolah Di Sekolah Umum Dan Sekolah Luar Biasa (SLB) - Indra, A.A.Istri Pritha Anindita; Widiasavitri, Putu Nugrahaeni (Jurnal Psikologi Udayana, 2015)
Quadriplegic is a term that is used as the identification of individual who have difficulty in optimizing the function of the body. Various obstacles faced by raising various negative reactions from the quadriplegic. Types of schools chosen by the individual quadriplegic as a means to get an education can bring out difference in environmental conditions encountered, which will certainly affect the learning performance of the individual. Outside of the phenomenon, uniquely, researcher found that there were cases of quadriplegic who attended public school and extraordinary school, which are able to accept the condition of themselves to be able to achieve the achievement in adolescence. Self-acceptance is an individual consciousness to accept the conditions of self as it is, which self-acceptance is one of the individual development task that are in the age range in adolescence. Based on this thing, the researcher is interested to find out about the process of self-acceptance on meritorious quadriplegic adolescent. This study used a qualitative research method with case study research design. Respondents in this study can be divided into two categories based on gender that is male and female, which in each category used each number one respondent. The result of this study indicates that there are three phases passed by quadriplegic adolescents in the process of self-acceptance, which is the initial phase, conflict phase, and the receiving phase. There are some differences in the dynamics at each phase that passed between male and female quadriplegic adolescents.   Keywords: self-acceptance process, quadriplegic adolescent, meritorious, public school, extraordinary school.